(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Increase in landuse development and human activities have significant influence on the occurrence of emerging pollutants (EPs) in water bodies such as rivers. As rivers are the main source of water supply in Malaysia, a study was conducted to determine the occurrence of EPs in one of the drinking water sources, namely Skudai River. Samples were collected five times at eight sampling points from the upstream up to the water intake of the river. Sample pre-treatment was performed by solid-phase extraction (SPE), whereas the analyses of the EPs were performed by Liquid Chromatography-Mass Spectrometry (LCMS-MS QTOF). Results showed that about 50 compounds were detected and fall into categorise as pharmaceuticals, Personal Care Products (PCPs), and Endocrine Disrupting Chemical (EDC). The most prevalent (75-100%) compounds detected were of these categories, whereas the least (less than 40%) were mainly pharmaceuticals. The concentration of styrene, a health-hazards EPs ranged from 45.11 to 203.48 µg/L with increasing trend towards downstream of the river. Based on the landuse data of Skudai River Basin, the study concluded that human activity, landuse, and environmental factors could possibly contribute to the presence of the EPs in the river.